Rising to the challenge? Inter-individual variation of the androgen response to social interactions in cichlid fish - Félix, Ana Sofia (2021)
The Challenge Hypothesis (Wingfield et al. Am. Nat. 136, 829-846) aims to explain the complex relationship between androgens and social interactions. Despite its well acceptance in the behavioral endocrinology literature, several studies have failed to found an androgen response to staged social interactions. Possible reasons for these inconsistencies are the use of single sampling points that may miss the response peak, and the occurrence of inter-individual variability in the androgen response to social interactions. In this study we addressed these two possible confounding factors by characterizing the temporal pattern of the androgen response to social interactions in the African cichlid, Oreochromis mossambicus, and relating it to inter-individual variation in terms of the individual scope for androgen response (i.e. the difference between baseline and maximum physiological levels for each fish) and behavioral types. We found that the androgen response to territorial intrusions varies between individuals and is related to their scope for response. Individuals that have a lower scope for androgen response did not increase androgens after a territorial intrusion but were more aggressive and exploratory. In contrast males with a higher scope for response had fewer aggressive and exploratory behaviors and exhibited two peaks of KT, an early response 2-15 min after the interaction and a late response at 60-90 min post-interaction. Given that the pharmacological challenge of the Hypothalamic-Pituitary-Gonad axis only elicits the late response, we suggest that these two peaks may be regulated by different physiological mechanisms, with the early response being mediated by direct brain-gonad neural pathways. In summary, we suggest that determining the temporal pattern of the androgen response to social interactions and considering inter-individual variation may be the key to understanding the contradictory results of the Challenge Hypothesis.